Local control and survival after stereotactic radiosurgery for colorectal cancer brain metastases: an international multicenter analysis - Bin-Alamer, Othman; Abou-Al-Shaar, Hussam; Singh, Raj; Mallela, Arka N; Legarreta, Andrew; Bowden, Greg; Mathieu, David; Perlow, Haley K; Palmer, Joshua D; Elhamdani, Shahed; Shepard, Matthew; Liang, Yun; et al. (Journal of neurosurgery, 2024)
OBJECTIVE: The goal of this study was to characterize local tumor control (LC), overall survival (OS), and safety of stereotactic radiosurgery for colorectal brain metastasis (CRBM). METHODS: Ten international institutions participating in the International Radiosurgery Research Foundation provided data for this retrospective case series. This study included 187 patients with CRBM (281 tumors), with a median age of 62 years and 56.7% being male. Most patients (53.5%) had solitary tumors, although 10.7% had > 5 tumors. The median tumor volume was 2.7 cm3 (IQR 0.22-8.1 cm3), and the median margin dose was 20 Gy (IQR 18-22 Gy). RESULTS: The 3-year LC and OS rates were 72% and 20%, respectively. Symptomatic adverse radiation effects occurred in 1.6% of patients. In the multivariate analysis, age > 65 years and tumor volume > 4.0 cm3 were significant predictors of tumor progression (hazard ratio [HR] 2.6, 95% CI 1.4-4.9; p = 0.003 and HR 3.4, 95% CI 1.7-6.9; p < 0.001, respectively). Better performance status (Karnofsky Performance Scale score > 80) was associated with a reduced risk of tumor progression (HR 0.38, 95% CI 0.19-0.73; p = 0.004). Patient age > 62 years (HR 1.6, 95% CI 1.1-2.3; p = 0.03) and the presence of active extracranial disease (HR 1.7, 95% CI 1.1-2.4; p = 0.009) were significantly associated with worse OS. CONCLUSIONS: Stereotactic radiosurgery offers a high LC rate and a low rate of symptomatic adverse radiation effects for the majority of CRBMs. The OS and LC favored younger patients with high functional performance scores and inactive extracranial disease.
Keywords: dospělí; brain metastasis; stereotactic radiosurgery; kolorektální nádory; Female; Adult; výsledek terapie; ženské pohlaví; Colorectal Neoplasms; colorectal cancer; nádory mozku; lidé; Gamma Knife radiosurgery; local tumor control; Treatment Outcome; míra přežití; tumor; radiochirurgie; retrospektivní studie; Radiosurgery; oncology; Male; Aged; Brain Neoplasms; Survival Rate; lidé středního věku; senioři; mužské pohlaví; overall survival; Retrospective Studies; Middle Aged; Humans